Anthropometric and physical performance profiles of high school age american football players: 11th and 12th grade Japanese athletes - Yamashita, D.; Yamaguchi, S.; Hernandez, F. A.; Yuasa, Y. (Journal of Science in Sport and Exercise, 2023)
Purpose: To compare anthropometric and physical performance profiles of Japanese 11th and 12th grade American football players within each positional group. Methods: Fifty-two 11th and 12th grade American football players from two Japanese high schools participated in the study during the summer pre-season period. They performed anthropometric (height and body mass) and physical (vertical jump, broad jump, 40-yard dash, pro-agility shuttle 4-kg medicine ball chest throw, front throw, and back throw) testing. Vertical jump momentum and 10-yard sprint momentum were also calculated by multiplying the velocity and body mass. Athletes were divided into two groups by playing positions: skill players and linemen. Results: Skill players in the 12th grade were better at medicine ball chest throw (d = 0.73, P = 0.04) and vertical jump momentum (d = 0.75, P = 0.03) than those in the 11th grade. However, there were no differences in any measurements (P > 0.05) between linemen from the two grades. Conclusion: The current study suggests that upper and lower body absolute power and momentum production can be improved for skill players even over 17 years old. On the other hand, body size and speed, attributes that did not change between 11th and 12th grades, seem to be essential talent identification criteria in the current environment. Further study is needed to monitor longitudinal performance improvements in implementing talent development programs by focusing on the quality of speed, agility and power development at the youth level.